Double arterial cannulation versus right axillary artery cannulation for acute type A aortic dissection: a retrospective study - He Zhang (BMC, 2021)
Abstract Background Cannulation strategy in surgery for acute type A aortic dissection (ATAAD) remains controversial. We aimed to retrospectively analyze the safety and efficacy of double arterial cannulation (DAC) compared with right axillary cannulation (RAC) for ATAAD. Methods From January 2016 to December 2018, 431 ATAAD patients were enrolled in the study. Patients were divided into DAC group (n = 341) and RAC group (n = 90). Propensity score matching analysis was performed to compare the early and mid-term outcomes between these two groups. To confirm the organ protection effect by DAC, intraoperative blood gas results and cardiopulmonary bypass parameters were compared between the two groups. Results Demographics and preoperative comorbidities were comparable between two groups, while patients in DAC group were younger than RAC group (51.55 ± 13.21 vs. 56.07 ± 12.16 years, P < 0.001). DAC had a higher incidence of limb malperfusion (18.2% vs. 10.0%, P = 0.063) and lower incidence of coronary malperfusion (5.3% vs. 12.2%, P = 0.019). No significant difference in cardiopulmonary bypass and cross-clamp time was found between the two groups. The in-hospital mortality was 13.5% (58/431), while there was no difference between the two groups (13.5% vs. 13.3%; P = 0.969). Patients who underwent DAC had higher incidence of postoperative stroke (5.9% vs. 0%, P = 0.019) and lower incidence of postoperative acute kidney injury (AKI) (24.7% vs. 40.3%; P = 0.015). During a mean follow-up period of 31.8 (interquartile range, 25–45) months, the overall survival was 81.5% for DAC group and 78.0% for RAC group (P = 0.560). Intraoperative blood gas results and cardiopulmonary bypass parameters showed that DAC group had more intraoperative urine output volume than RAC group (P = 0.05), and the time of cooling (P = 0.04) and rewarming (P = 0.04) were shorter in DAC group. Conclusions DAC will not increase the surgical risks compared to RAC, but could reduce the incidence of postoperative AKI which may be benefit for renal protection.